Effect of sodium hydroxide on flow and strength of fly ash based geopolymer mortar - Patankar, Subhash V.; Jamkar, Sanjay S.; Ghugal, Yuvraj M. (Journal of Structural Engineering, 2024)
Concrete/ mortar are used in most of the civil construction work in the world. However, high energy requirement and pollution involved in the production of cement hampers the image of cement-based products as sustainable materials. Efforts are continuously being made to make concrete environmentally friendly. Geopolymer is a new development in the world of concrete in which cement is totally replaced by fly ash and activated by alkaline liquids to act as a binder in the concrete/mortar mix. Experimental investigation has been carried out to study the effect of concentration of sodium hydroxide, temperature and its duration on flow and compressive strength. Activated liquid to fly ash ratio of 0.40 by mass was maintained in the experimental work on the basis of past research. Sodium silicate solution with Na2O = 16.37%, SiO2 = 34.35% and H2O = 49.28% was considered. The concentration of sodium hydroxide solution is varied as 2.91, 5.6, 8.1, 11.01, 13.11 and 15.08 Moles. Geopolymer mortar cubes of 70.7 mm side were cast. The temperature of curing was varied as 60, 90, and 120°C and the duration of curing for each temperature as 6, 12, 18 and 24 hours after demoulding. Test results show that the flow of geopolymer mortar increases with increase in the concentration of sodium hydroxide. The compressive strength of geopolymer mortar increases with increase in duration of heating at constant temperature. Temperature also plays vital role in accelerating the strength, however beyond 90°C the rate of gain of strength is mainly depend on concentration of sodium hydroxide solution.